Realizing healthy culinary tourism through education in the ‘Angkringan’ street vendor community of Yogyakarta city during the COVID-19 pandemic - Rizka Ayu Setyani; Fika Lilik Indrawati; Tri Mei Khasana (Journal of Community Empowerment for Health, 2022)
Angkringan is included in the culinary options of Java, although it involves a simple food stall on the roadside using a wheelbarrow and covered with a plastic tarpaulin as the roof.However, food safety is one of the main factors that influence tourists in choosing Angkringan culinary spots. Therefore, it is necessary to monitor the quality of food management by paying attention to health requirements including hygiene and sanitation procedures. This study aimed to analyze the differences in the food safety scores of Angkringan street vendors in Yogyakarta City before and after an intervention. We conducted a quantitative study with an experimental design from March to May 2021. We intervened with health education through pocketbooks in 49 communities of Angkringan street vendors in Yogyakarta tourism locations with a duration of one month. Data collection was conducted through the Food Safety Score Questionnaire while data analysis used Wilcoxon signed-rank tests. The majority of Angkringan street vendors had a category of Food Safety Score that was vulnerable but safe to consume before and after the pocketbook intervention. However, the influence of the intervention showed significant differences in research results (p-value < 0.05). This study concluded that health education interventions with pocketbooks among the Angkringan street vendors could positively affect food safety scores. We recommend that the government foster food hygiene education and monitoring of Angkringan street vendors, especially during the COVID-19 pandemic.